Analiza zawartości protokołów posiedzeń Białoruskiego Klubu Poselskiego z lat 1922–1924 - Dudkin, Aŭgen (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2024)
The analysis of the minutes of the Belarusian Parliamentary Club meetings held between 1922 and 1924 shows that the Belarusians actively participated in the intra-club and parliamentary activity; nevertheless, the effectiveness of their activity depended on the degree of their competence, ability to reliably and punctually carry out the formulated plans, and realistic assessment of the political situation, affecting the possibility of effectiveness of their political activity and fulfilment of pre-election promises.
p. 41-65 : illustrations
Summary in English and Russian.
Keywords: Republic of Poland; parliamentary elections; Sejm; electoral law; electoral districts; national minorities; voters; electoral agitation; voting results; Poland - 1918-1939 (Second Polish Republic) - politics and government; Belorussians (nation) - Poland - 1900-1945; Poland. Sejm Rzeczypospolitej Polskiej (1922-1939); minorities - government policy - Poland - 1900-1945